LARGE-SCALE GIS-BASED HYDROGEOLOGICAL MODELING OF FLANDERS: A TOOL FOR GROUNDWATER MANAGEMENT - Cools Ja.; Meyus Y.; Woldeamlak S.T.; Batelaan O.; De smedt F. (My University, 2006)
For the implementation of the European Union Water Framework Directive (WFD), technological and scientific support are required. This paper presents a methodology to support a first step of the implementation of WFD, which is the delineation of groundwater bodies. The methodology consists of (1) the development of a complete and generally-accepted hydrogeological classification system for Flanders, named the HCOV code, (2) the development of a geographic information systems (GIS)-managed borehole database, and (3) the development of aquifer and aquitard models by means of a solid modeling approach. For each unit of the hydrogeological classification code for Flanders unit, GIS maps are generated for the three basic characteristics of hydrogeological layers: extent, base level and thickness, such that combined, the volume and extent of a hydrogeological layer is unambiguously defined. This GIS-based hydrogeological database has become a useful tool for groundwater management purposes and to provide the input for groundwater modeling.
Keywords: HYDROGEOLOGICAL MODELLING; GIS BOREHOLE DATABASE; AQUIFER MODELS; AQUITARD MODELS; BELGIUM